O4B.3 The impact of income support systems on healthcare quality and functional capacity in workers with LBP: a realist review. (April 2019) - Donato, Michael Di; Iles, Ross; Lane, Tyler; Collie, Alex
Abstract : Background: Low back pain (LBP) is a leading cause of work disability. While absent from work, workers with LBP may receive income support from a system such as workers' compensation or social security. Current evidence suggests that income support systems can influence recovery from LBP, but provides little evidence as to why and how these effects occur. This study examines how and in what contexts income support systems impact the healthcare quality and functional capacity of people with work disability and LBP. Methods: We performed a realist review, a type of literature review that seeks to explain how social interventions and phenomena in certain contexts generate outcomes, rather than simply whether or not they do. Five initial theories about the mechanisms of the relationship were developed, tested, and refined by acquiring and synthesising academic literature from purposive and iterative electronic database searching. This process was supplemented by grey literature searching for policy documents and legislative summaries, and semi-structured interviews with experts in income support, healthcare, and LBP. Results: Income support systems influence healthcare quality through healthcare funding restrictions, healthcare provider administrative burden, and allowing an employer to select healthcare providers. Income support systems influence worker functional capacity through the level of participation and share of income support funding required of employers, and through certain administrative procedures. These mechanisms are often exclusively context-dependent, and generate differing and unintended outcomes depending on features of the healthcare and income support system, as well as other contextual factors such as socioeconomic status and labour force composition. Conclusion: Income support systems impact the healthcare quality and functional capacity of people with work disability and LBP through context-dependent financial control, regulatory, and administrative mechanisms. Future policy design and research efforts should consider how income support systems may indirectly influence workers with LBP via the workplace.